Bivariate grid-connection speed control of hydraulic wind turbines. Issue 1 (January 2021) - Ai, Chao; Gao, Wei; Chen, Lijuan; Guo, Jiawei; Kong, Xiangdong; Plummer, Andrew
Abstract: The requirement for An electrical grid-connected wind turbine is that the synchronous generator speed is stable within a required speed range for the electrical grid. In this paper, a hydraulic wind turbine (HWT) system is considered, and the working principle and working conditions of the HWT are introduced. A novel speed control method is proposed in this paper, using both a proportional flow control valve and a variable displacement motor, which are adjusted in combination to control the speed of the HWT. By establishing a state space model of the HWT and solving the nonlinear system with a feedback linearization method, a bivariate tracking controller is constructed to realize accurate speed control under fluctuating wind speed and the load disturbance conditions. The effectiveness of the control method is verified by simulation, but experimental results highlight problems with the method. The theoretical controller is simplified to reduce sensitivity to measurement noise and modeling error. The control effect has been improved to some extent, but it is limited. Based on these results, combined with the sliding mode variable structure control method and the feedback linearization method to solve the problem of measurement noise and modeling error, and the effectiveness of the control law is finally verified experimentally. It lays a theoretical foundation for the practical application of HWT.